Chronically Elevated Corticosterone Levels, via Cocoa Butter Injections of Corticosterone, Do Not Affect Stress Response, Immune Function, and Body Condition in Free-living Painted Turtles (Chrysemys picta) - Juneau, Véronique (Université d'Ottawa / University of Ottawa, 2014)
Chronic stress can result in elevated circulating levels of glucocorticoid hormones in vertebrates, which can affect their stress response, their immune function, and eventually their fitness. I tested the effect of chronic corticosterone (CORT) elevation on the acute stress responsiveness, immune function, and body condition of free-living painted turtles (Chrysemys picta) in Gatineau Park, using slow-release exogenous CORT administration. While Silastic implants did not predictably elevate circulating CORT concentrations in painted turtles, injections of CORT-laden cocoa butter kept circulating levels elevated for up to 3 weeks, to concentrations likely physiologically and ecologically relevant for the species. I measured the acute CORT stress response, parasitaemia, heterophil-to-lymphocyte ratios, and total leukocyte counts after 1 week and 3 weeks, and determined body condition after 1 week, 3 weeks, and 1 year. Compared to sham and control turtles, I observed no effect of treatment on these hormonal, immune, and body condition metrics of stress, possibly because CORT mediates resource allocation only in the presence of additional immune or energy challenges, because of the masking effect of extrinsic factors, or because free, not total, CORT appears to be biologically active.
Keywords: Baseline; Blood parasite; Chelonian; Chronic stress; Corticosterone manipulation; Ectotherm; Glucocorticoid; Haemogregarina balli; Heterophil-to-lymphocyte ratio; Leukocyte count; Reptile; Silastic implant; Stress-induced